Literature as Ideological Intervention: Palestinian Resistance in Elias Khoury’s Awlād al-Ghīṭū - Icha Firza Sari; Rizqi Handayani (Postgraduate of IAIN Metro Lampung Indonesia, 2025)
This study examines the ideology of Palestinian resistance in Elias Khoury’s Awlād al-Ghīṭū: Ismī Ādam through the perspective of literary sociology. Grounded in the historical experience of the 1948 Nakbah, the study conceptualizes the Nakbah not as a singular past event but as an ongoing colonial condition that continues to shape Palestinian life through spatial control, legal exclusion, and epistemic violence. The analysis focuses on Khoury’s ideological framework, particularly his critique of colonialism and imperial domination, the role of collective memory as a form of resistance, and the positioning of literature as a medium of social transformation. Through qualitative textual analysis supported by relevant secondary literature, the article explores the novel’s narrative structure, characterization, and memory discourse. The findings demonstrate that Khoury articulates an ideology of resistance by transforming collective memory into a counter-hegemonic force that resists historical erasure and sustains Palestinian identity. The novel further frames literature as a site of alternative education, economic solidarity, and cultural affirmation, revealing colonial violence as multidimensional, extending beyond material dispossession to symbolic and cognitive domination. Ultimately, Awlād al-Ghīṭū: Ismī Ādam functions not merely as an aesthetic work, but as a political and epistemic intervention that affirms the enduring role of literature in confronting modern colonial power.